Municipal Sukuk as an Alternative Source of Aceh Development Fund - Fadhillah, Muhammad Haris; Sari, Nurma; Sartiyah, Sartiyah; Sitepu, Novi Indriyani; Nurlina, Eka (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
This study explores the understanding of perception of opportunities of issuance, obstacles and strategies towards the development of Municipal Sukuk in Aceh. The research method used is descriptive qualitative, with data collection techniques used including (1) Interviews with Various Stakeholders including local and financial authorities, academia, and regional house of representatives related to the municipal sukuk of Aceh, (2) Documentation conducted through photos and recorders and (3) Triangulation. The study results show that Municipal Sukuk is an Alternative financial instrument to the special autonomy fund, which has a great opportunity for implementation in Aceh. This study also reveals several obstacles, such as Lack of readiness in the Aceh’s local government related to Municipal Sukuk issuance. This study proposes several development strategies that can be carried out, including forming a joint team to accelerate the issuance of Municipal Sukuk, making Municipal Sukuk one of the main topics of MUSRENBANG (Musyawarah Rencana Pembangunan/Development Plan Deliberation), holding scientific discussions and FGDs and increasing the socialization of Municipal Sukuk to various groups. This research carries out novel findings of the purpose of using Sukuk as an alternative to Aceh's development funds. The practical implications of this study are expected to increase awareness of the need for alternative financing as Aceh's development funds.